2012
DOI: 10.1049/el.2012.1459
|View full text |Cite
|
Sign up to set email alerts
|

Stack decoding of polar codes

Abstract: A successive cancellation stack (SCS) decoding algorithm is proposed to improve the performance of polar codes. Unlike the conventional successive cancellation decoder which determines the bits successively with a local optimal strategy, the SCS algorithm stores a number of candidate partial paths in an ordered stack and tries to find the global optimal estimation by searching along the best path in the stack. Simulation results in the binary-input additive white Gaussian noise channel show that the SCS algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
169
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(170 citation statements)
references
References 5 publications
0
169
0
1
Order By: Relevance
“…2 The Key Laboratory of Information Coding and Transmission, Southwest Jiaotong University, ErHuan Road, Chengdu, China. 3 The School of Computer Science and Technology, Xi'an Technological University, JinHua Road, Xi'an, China. 4 Border Defence Academy, HuanShan Road, Xi'an, China.…”
Section: Competing Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The Key Laboratory of Information Coding and Transmission, Southwest Jiaotong University, ErHuan Road, Chengdu, China. 3 The School of Computer Science and Technology, Xi'an Technological University, JinHua Road, Xi'an, China. 4 Border Defence Academy, HuanShan Road, Xi'an, China.…”
Section: Competing Interestsmentioning
confidence: 99%
“…One of the reasons is that the successive cancellation (SC) decoding for polar codes is suboptimal and it may cause error propagation due to the serial decoding architecture. Although there are some improved SC decoders [2,3], the throughput of these decoders is low and the decoding latency is relatively high. Another interesting decoding method for polar codes is belief propagation (BP) decoding [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The successive cancellation stack (SCS) [36] is proposed to reduce the complexity of SCL in some conditions. The SCL decoding can combine with cyclic redundancy check (CRC) in a concatenated coding fashion to further improve the performance of polar codes [11], which substantially outperformed the state-of-art turbo and LDCP codes.…”
Section: Successive-cancellation (Sc) Decodingmentioning
confidence: 99%
“…To further improve the performance of polar codes, Niu and Chen showed that, with CRC aided, the performance of SCL decoder becomes comparable to the state-of-the-art LDPC codes [3]. In order to improve the time and space complexity of the SC decoder, Niu proposed successive-cancellation stack (SCS) algorithms [4]. The successive-cancellation hybrid (SCH) algorithm combines the features of SCL and SC and approaches the performance of ML decoding with acceptable complexity [5].…”
Section: 이 논문은 교육부 및 한국연구재단의 기본연구에 의해 지 원되었음(Nrf-2014r1a1a2058152) *mentioning
confidence: 99%